Oceanographic drivers of the biogeographic patterns of ascidians species (Tunicata: Ascidiacea) along the western Atlantic coast - Velásquez Sayago, Marcel Alexander (2024)
The latitudinal diversity gradient (LDG) is a well-known phenomenon among many animal taxa across different geographical regions. However, the underlying environmental factors that drive these patterns are still unknown for many taxa. In the case of ascidians, a group of marine organisms within the chordate subphylum Tunicata and the closest living relative to vertebrates, the LDG has been studied for over two decades. Yet, a comprehensive understanding of the environmental variables that can best predict their biogeographic structure is still in its infancy. The purpose of this study is to assess the environmental factors that contribute to the latitudinal diversity gradient of 363 ascidian species and to examine the potential effects of climate change on six ascidians species along the Western Atlantic (WA) coast. This will be accomplished by using a Random Forest model and a multi-model ensemble approach with ten different algorithms. Specifically, this project aims to 1) evaluate the role of oceanographic variables in predicting the LDG of ascidian species along the WA, and 2) assess the potential impacts of climate change on the distribution of six ascidians species under the future climate change scenario SSP3-7.0 (Shared Socioeconomic Pathwayand) for the time periods [2040-2050] and [2090-2010]. Understanding the ecological variables that influence the distribution of ascidian species is crucial for advancing biogeography, ecology, and evolution research. Moreover, it can provide insights into how this group of marine invertebrates may respond to global climate change or anthropogenic disturbances. These are increasingly important research topics, especially in this era of accelerated climate change and anthropogenic pressures on the environment.